Configuración identitaria en jóvenes tras la desaparición forzada de un familiar (2015)
ABSTRACT: This study examines the configuration of identity among young people that experienced a relative’s enforced disappearance during their childhood. The authors adopted a qualitative approach, and using the theory of social constructionism, analyzed autobiographical narratives from seven young people (four females and three males) and five family members (mothers and grandmothers). The findings indicate that these young people formed their identities in violent social contexts in which families established social practices related to a relative’s forced disappearance. These young people have configured their identity within reconfigured families because of the uncertainty produced by the absence of that person, and due to a social compulsion to hide the disappearance behind silence. It was evidenced that there are two tendencies in the way these young people configure their identities: the first is based on reconstruction and the second is focused on loss.